ANALISIS PERCEPTUAL MAPPING MEREK GULA DASAMANIS DALAM PASAR GULA KEMASAN DI SURABAYA - Rochsianto, Novan Yoga (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: Positioning is part of a marketing strategy in winning thecompetition. By arranging a product that occupies a clear place, and is moredesirable than competing products, it makes the product strong and will lasta long time in winning the market competition. The purpose of this researchis to analyze the marketing strategy through the positioning of basic sugarproducts. By using the attributes of packaged sugar obtained from theconsumer intercept survey on 30 respondents who frequently purchasepackaged sugar. From these attributes it is used as a questionnaire and thedata will be analyzed using the cluster analysis method, factor analysis, andMDS. The results showed that there were 2 consumer segments inpurchasing packaged sugar. In addition, there are 2 strong dimensions thatinfluence consumers in purchasing packaged sugar. By using the marketingmix as a tool to design a marketing strategy in the development of Dasamanissugar marketing.Keywords: Positioning, Perceptual Mapping, Multidimensional scaling